Pendidikan Kaderisasi Kepemimpinan di Pondok Pesantren Menurut KH. Imam Zarkasyi dalam Pendidikan Islam - Tamsir Ahmadi (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
In Boarding School institution Kyai as supresme leader. His ability to lead greatly influences the course of the education process and the existence of boarding school. Not a few is some boarding school, some kiai only rely on their charisma to lead and careless about regeneration, as preparation for the next generation in leading pesantren. So when he pssed away, there are changes in leadership style by the next generation which is caused by various things. Whish has an impact on changes in policy making yhat are not based on pesantren values. The regeneration in pondok pesantren must be carried out whit the aim that the successor leaders have a strong foundation in leading, based on the values of pondok pesantren which have been instilled by it’s predecessor and not dependent on its charisma. In an effort to prepare the next leader in the boarding school K.H. Imam Zarkasyi believes that there are at least seven points that must be implemented and given to the cadres, starting from: direction, training, assignment, habituation, escort, availability and approaches. In a process, of course there are factors that support and inhibit those faced in order to produce qualified prospective leaders.